The Influence of Promotions and Prices on Purchase Decisions at Shopee (Case Study in Tanjung Piayu Community, Batam City) - Jubelia Ayu Ebong Hurek; David Humala Sitorus (eCo-Buss, 2023)
This study aims to determine the effect of promotions and prices on purchasing decisions at Shopee partially or simultaneously on purchasing decisions at Shopee. This research method is quantitative with the sampling technique in this study, namely probability sampling with the simple random side method. The distribution of questionnaires in this study used the simple random sampling technique and the data were analyzed using the SPSS version 25 statistical program. The results of this study indicated that promotions at Shopee significantly influence purchase decision making at Shopee with a significance of 0.000 <0.05 and t count 5.426 > 1,984. And with a significance result of 0.000 <0.05 and t count 4.378 > ttable 1.984, prices also have a significant effect on purchasing decisions at Shopee. It was concluded that promotions and prices had a significant effect on purchasing decisions at Shopee. According to the coefficient of determination for R Square of 0.579, the percentage effect of promotion and price on purchasing decisions at shopee in the Tanjung Piayu community in Batam City is 57.9% and the influence of other variables not included in this study is 42.1%.